Antiepileptogenesis and disease modification: Clinical and regulatory issues. Issue 3 (29th July 2021) - French, Jacqueline A.; Bebin, Martina; Dichter, Marc A.; Engel, Jerome; Hartman, Adam L.; Jóźwiak, Sergiusz; Klein, Pavel; McNamara, James; Twyman, Roy; Vespa, Paul
Abstract: This is a summary report of clinical and regulatory issues discussed at the 2018 NINDS workshop, entitled "Accelerating Therapies for Antiepileptogenesis and Disease Modification." The intent of the workshop was to optimize and accelerate development of therapies for antiepileptogenesis (AEG) and disease modification in the epilepsies. The working group discussed nomenclature for antiepileptogenic therapies, subdividing them into "antiepileptogenic therapies" and "disease modifying therapies, " both of which are urgently needed. We use the example of traumatic brain injury to explain issues and complexities in designing a trial for disease‐preventing antiepileptogenic therapies, including identifying timing of intervention, selecting the appropriate dose, and the need for biomarkers. We discuss the recent trials of vigabatrin to prevent onset and modify epilepsy outcome in children with tuberous sclerosis (Epistop and PreVeNT). We describe a potential approach to a disease modification trial in adults, using patients with temporal lobe epilepsy. Finally, we discuss regulatory hurdles for antiepileptogenesis and disease‐modifying trials.